Israeli graphic novels & the second Palestinian Intifada: 'Jamilti', Exit Wounds & Mike's Place. Issue 5 (3rd September 2021) - Reingold, Matt
ABSTRACT: The following paper analyzes Rutu Modan's and Jack Baxter and Joshua Faudem's graphic texts about the Second Palestinian Intifada and its impact on Israeli society in the early 2000s. Modan's position as an Israeli and Baxter's position as an American lead to different approaches to presenting the narrative. Baxter's place as an outsider leads him to focus his text on the specific details on the bombing itself as he tries to understand how terror affects a group of Israelis. Conversely, as an insider, Modan approaches her texts with a pre-existing awareness of Israeli society and she instead focuses on how Israelis have become habituated to a life under the threat of violence. Considered together, the authors present parallel explorations of how insiders and outsiders can come to understand the myriad ways that terror impacts a society.